The Long-Term Effects of Air Pollution on Health and Labor Market Outcomes: Evidence from Socialist East Germany - Moritz Lubczyk; Maria Waldinger (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
What are the long-run effects of sustained exposure to air pollution? A unique natural experiment allows us to examine this question. In 1982, a sudden cut in Soviet oil forced Socialist East Germany to switch to highly polluting lignite coal. While the shock sharply increased air pollution near mining regions, authoritarian restrictions on mobility, housing, and jobs prevented sorting responses. We document persistent labor market impacts over three decades. Exposed individuals work less, earn lower wages, and retire earlier. Health is a key mechanism: infant mortality rises by 9% and the long-run incidence of asthma and cardiopathy increases significantly.
Keywords: I15; J24; J60; N54; Q53; 330; air pollution; labour supply